Virtual cycling effort is dependent on power update rate - Lazzari, C. D.; Diefenthaeler, F.; Marques, J. L. B. (European Journal of Sport Science, 2020)
Cycling ergometer protocols are commonly integrated with a virtual reality environment (VRE), especially because of its static position that also allows multiple exercise experiments. Concerning VRE scenarios, visually delayed situations like the ones produced at excessive low update rates can also affect the sense of presence and physiological responses. However, the main interface between the subject and a cycling VRE is the power applied over the crank, and there are only a few experiments to evaluate the effect of delayed situations on this particular interface. Thus, this work aims to investigate the effects of the power update rate (PUR) over the subject`s performance on an avatar-based simulator during a drafting task. A custom cycling VRE was built, and 21 male recreational cyclists (175.9 ± 7.5 cm; 76.5 ± 13.9 kg) were tested at six different PUR levels from 100 to 3000 ms. As a result, PUR affects performance scores (virtual distance, efficiency, and heart rate, p < 0.01) at the given VRE conditions. The case-by-case analysis of the groups reveals that higher update rates always lead to a statistical equivalent or superior performance. Nevertheless, no parameter shows any group difference between 500 ms and lower PUR. These results suggest that virtual cycling protocols should consider PUR and other delay-related mechanisms as possible intervening factors over physiological responses and performance scores.